2019
DOI: 10.24191/ajue.v15i3.04
|View full text |Cite
|
Sign up to set email alerts
|

Millennial Learners’ Acceptance and Satisfaction of Blended Learning Environment

Abstract: Teaching in an era dominated by millennials represents a challenging task for educators in Institutes of Higher Learning (IHLs). One distinct feature in teaching millennials is the advancement in digital learning which has improved learning styles in higher education. Besides face-to-face interactions with the instructors, the blended learning approach has been introduced in many courses to cater to the needs of millennial learners. This study aims to provide an insight into on students’ acceptance and satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The concept of BL was introduced to most disciplines by combining the traditional face-to-face teaching and online communications. It is aimed to prepare the students for self-directed learning, the overall satisfaction towards the theory and real practices are still scarce (Abu Seman, Hashim, Mohd Roslin, Mohd Ishar, 2019). Since the use of i-Learn was not compulsory, many lecturers chose other more user-friendly and free platforms such as Google Classroom and other social media such as WhatsApp, Telegram and YouTube (Chung et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of BL was introduced to most disciplines by combining the traditional face-to-face teaching and online communications. It is aimed to prepare the students for self-directed learning, the overall satisfaction towards the theory and real practices are still scarce (Abu Seman, Hashim, Mohd Roslin, Mohd Ishar, 2019). Since the use of i-Learn was not compulsory, many lecturers chose other more user-friendly and free platforms such as Google Classroom and other social media such as WhatsApp, Telegram and YouTube (Chung et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of a blended-learning approach is supported by a large body of recent literature on the success criteria of e-learning systems for deployment with marginalized target groups. The design of blended-learning approaches and their fit to the context of deployment have significant impact on student satisfaction (Alomari et al, 2020 ; Seman et al, 2019 ; Zhang & Dang, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In numerous studies, the technically oriented D&M IS Success Quality dimensions, information quality, service quality and system quality have been examined with respect to the success of information systems, e-learning systems as well as in special studies on blended-learning systems. Not all of these studies found significant support for all three success factors (Mohammadi, 2015 ; Seman et al, 2019 ; Wu et al, 2010 ; Zhang & Dang, 2020 ). In the present study, we could show that of these factors, indeed only information quality had a significant impact on task-technology-fit and all other paths could not be confirmed to be relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that the students were contented as presented with the rate cumulatively more than 80% for Strongly Agree and Agree. According to Abu Seman, Hashim, Roslin & Mohd Ishar (2018), we have to be creative to get the attention of the millennial to focus in the class. Thus, it could be surmised that through the scaffolding method, teaching and learning have become more effective and interesting as students can equip themselves with the soft skills and new technologies that they will be dealing with within the job market (Hawa, Rohaidah, Mohd Hairul Anuar, Nor Huda & Nurhazlini, 2019) and experience the learning by doing.…”
Section: Fig 2 Poster -Unlock the New Youmentioning
confidence: 99%